Purpose of the measurement of intraoperative hepatic hemodynamics in liver transplant surgery - Pablo Lozano; Lorena Martín; Maitane Orue-Echebarria; José Manuel Asencio; Hemant Sharma; Jose Ángel López Baena (Archives of Organ Transplantation - Peertechz Publications, 2019)
Liver graft function depends on different biological factors that are related to the donor, the recipient and the potential damage arising from the organ preservation technique. However, adequate hepatic artery flow and portal vein flow rates ensure a sufficient flow of oxygen and nutrients in order to ensure a suitable cellular graft function after the extreme metabolic decrease condition induced by hypothermia and the preservation solution. Liver inflow is a highly complex system due to its double irrigation system. These two systems are connected by the well-known "hepatic arterial buffer response" concept. This mechanism explains changes in hepatic arterial flow (HAF) as a compensation for changes in the portal vein flow (PVF), so that the hepatic artery adjusts total flow in relation to alterations in the portal blood flow. At the moment, the minimum HAF and PVF required for an adequate regeneration and functional recovery of the liver graft have not been yet established. The hyperdynamic circulation state observed in cirrhosis could influence liver hemodynamics during liver transplantation; with this situation can be modified intraoperative surgical maneuvers if necessary. A decrease in the HAF could lead to hepatic artery thrombosis. The changes in microcirculation also play an important role in the damage caused by the ischemia reperfusion injury; for instance, sinusoidal diameter narrowing and vascular flow are the first changes to occur after damage by ischemia reperfusion. The damage produced in the sinusoidal endothelium manifests itself as alterations in the early stages of intraoperative hemodynamics. Therefore, and in conclusion, early intraoperative detection of alterations in liver hemodynamics during liver transplantation could be used to prevent worse outcomes in the postoperative time.